PENGARUH PERSEPSI KEMUDAHAN DAN PERSEPSI KEGUNAAN TERHADAP PENERIMAAN PENGGUNA SISTEM INFORMASI AKADEMIK TERPADU - Ayatulloh Michael Musyaffi; Arinal Muna; Nelia Fariani (JRAK: Journal of Accounting Research and Computerized Accounting, 2016)
The purpose of this research is to evaluate the influence of perceieved usefulness and perceived ease of use to acceptance of SIKADU (Sistem Informasi Akademik Terpadu/academic information system) at Swadaya Gunung Jati University (Unswagati), based on student perception. The urgency of this study is this system just implemented by university. Using slovin method, the sample use 259 accounting students of 773 accounting students. Partial Least Square is used for data analysis. The results show, that perceived usefulness and perceived ease of use can influence the acceptance of SIKADU. Further, perceived ease of use have the most influence to acceptance of SIKADU. It means the most important of acceptance of SIKADU is ease of use than the usefulness of SIKADU it self.